Receipts & expenditure account - week ending 22nd March 1940
1940-03 038-0046-002 BASQUE CHILDREN'S COMMITTEE. RECEIPTS & EXPENDITURE ACCOUNT - WEEK ENDING 22nd March 1940. Balance brought forward 15th March. 654:17: 0 add. Friends Service Council. 140: 0: 0 Shapcott - Refund of Commission. 8:17: 6 General Donations. 7:17: 6 Rail Vouchers. 5: 4: 1 Sale of Typewriter 2: 0: 0 Maintenance cheques cancelled: Kerr. 2:10: 0 Laleham. 6:10: 0 9: 0: 0 Basque Song Book. 2: 6 173: 1: 7 827:18: 7 less Expenditure. 611:17: 3 Balance as per Cash Book. £ 216: 1: 4 Expenditure. Maintenance.: Aylesbury. 50; 6: 0 Carshalton. 6: 0: 0 Plymouth. 4:10: 0 Barnet. 2:10: 0 63: 6: 0 Barnet - Adoption reforwarded. 10: 0 Dilapidations - Laleham. 400: 0: 0 Gt. Western Railway. 34: 1: 3 Connelly - Repairs. 1:8: 0 Clothing. 4: 8: 3 Older Boys Fund. Maintenance: Birmingham. 3:14: 8 Wednesbury. 2:10: 0 Dudley. 2: 9:11 boys at Polikoff. 1:15: 1 Various Localities. 3: 9: 0 13:18: 8 Fares, Pocket Money etc. London. 17: 4 " " " " Birmingham.2:15: 0 Salaries & Insurance. 6: 2:10 23: 18:10 527: 7: 4 Office Charges: Salaries. 19: 1: 7 Telephone. 59:13: 0 Petty Cash: Postage.2:16:10 Fares. 12: 2 Exes re Transfers 11: 4 Tea & Milk 2: 0 Cleaners & Polish. 11: 0 Salary- Senor Gomez. 1: 2: 0 5:15: 4 84: 9:11 £ 611:17: 3 Liabilities. Railway & Sundry Accounts. £280. Part of Railway Accounts to be charges to Refugee and Repatriation Accounts. 292/946/38/46(II)